National health insurance from the worker's standpoint - Duffy, L. J. (Statistical and Social Inquiry Society of Ireland, 1928)
Before proceeding to consider the manner in which the intention of the Act in regard to the prevention and cure of illness has been fulfilled it may be convenient to examine the extent to which the monetary assistance made available by the scheme is availed of.
Symposium on national health insurance
Read before the Society on April 26th, 1928
Keywords: National health insurance; Public health; 314.15